2012
DOI: 10.1183/09031936.00189011
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis-associated common variable immunodeficiency disorder: a case-control study versus sarcoidosis

Abstract: The aim of the present study was to investigate to what extent interstitial lung disease (ILD) in common variable immunodeficiency disorder (CVID)-associated granulomatous disease (GD) is similar to pulmonary sarcoidosis 20 patients with CVID/GD were included in a retrospective study conducted by the Groupe Sarcoïdose Francophone. Medical records were centralised. Patients were compared with 60 controls with sarcoidosis.Clinical examination showed more frequent crackles in patients than controls (45% versus 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 26 publications
3
92
3
1
Order By: Relevance
“…The second patient did not receive any therapy directed at the GD. However, both of them improved in clinical, analytical, and radiological terms, which is in line with the favorable evolution reported by Bouvry et al 1 The appropriate treatment for GD-CVID patients has not yet been established. 6,7,12,15 There are no protocols regarding diagnosis, treatment and follow-up, nor prognosis for GD-CVID patients.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The second patient did not receive any therapy directed at the GD. However, both of them improved in clinical, analytical, and radiological terms, which is in line with the favorable evolution reported by Bouvry et al 1 The appropriate treatment for GD-CVID patients has not yet been established. 6,7,12,15 There are no protocols regarding diagnosis, treatment and follow-up, nor prognosis for GD-CVID patients.…”
supporting
confidence: 59%
“…1 It is defined by markedly reduced serum concentrations of IgG, combined with low levels of IgA and/or IgM, poor or absent response to immunizations in a patient without any other signs of immunodeficiency. The prevalence in Europe is estimated to be around 1:50,000---1:200,000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by BOUVRY et al [1] regarding similarities and differences between interstitial lung disease (ILD) in granulomatous common variable immunodeficiency (CVID) and sarcoidosis. In this retrospective study, differential bronchoalveolar lavage (BAL) cytology was analysed in 14 patients with granulomatous CVID and ILD.…”
Section: To the Editormentioning
confidence: 97%
“…Unlike the sarcoidosis group (5.3¡4.0), the CD4/CD8 ratio was low in the analysed patients with granulomatous CVID and ILD (1.6¡1.1, n510) and even ,1 in half of the patients (n55). BOUVRY et al [1] concluded that there are significant differences in differential BAL cytology between sarcoidosis and granulomatous CVID.…”
Section: To the Editormentioning
confidence: 99%